Role of Ulama Ijma in Legitimizing and Validating Sharia Banking Practices in Indonesia - Baidhowi Baidhowi; Chatrine Novianti Sitanggang; Dinda Merry Wijarningsih; Najua Rahmawati; Sahda Naura Salwa Taufiqi; Veny Gambini Tampubolon (Department of Sharia Economic Law, 2025)
This study discusses the role and position of ijma' ulama as the basis of Islamic law and its influence in determining the validity of Islamic banking practices in Indonesia. Ijma' means the consensus of scholars in determining the law on issues that are not directly explained in the Qur'an and hadith. In modern times, ijma' has become an important means of addressing new issues in the economic and financial fields in order to remain consistent with Islamic teachings. This study uses a literature review method by examining sources of Islamic law, Islamic banking regulations, and fatwas issued by the National Sharia Council-Indonesian Ulema Council (DSN-MUI). The results of the study show that ijma' ulama plays a major role in ensuring that Islamic banking activities are in accordance with Islamic principles. Through deliberations among Islamic scholars and economists, the DSN-MUI issues fatwas that serve as guidelines for Islamic banks in providing their products and services. These fatwas are also recognized by the state through Law No. 21 of 2008 on Islamic Banking, giving them official legal force. Thus, ijma' not only serves as a religious guideline, but also as a bridge between Islamic teachings and state law. Through the role of ijma', Islamic banking practices in Indonesia can be carried out in accordance with the values of justice, honesty, and balance as taught in Islam. Keywords: Ijma' Ulama, Islamic Law, DSN-MUI Fatwa, Islamic Banking, Legal Validity